2010
DOI: 10.1039/b924574j
|View full text |Cite
|
Sign up to set email alerts
|

Looking for heteroaromatic rings and related isomers as interstellar candidates

Abstract: Finding complex organic molecules in the interstellar medium (ISM) is a major concern for understanding the possible role of interstellar organic chemistry in the synthesis of prebiotic species. The present interdisciplinary report is a prospective study aimed at helping detection of heteroaromatic compounds or at least of some of their isomers in the ISM. The thermodynamic stabilities of the C(4)H(5)N, C(4)H(4)O, C(4)H(4)S families were calculated using density functional theory (DFT). It was found that pyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Four out of seven of the aforementioned most stable isomers (noted Isomer Obs. ) have been identified in the ISM in agreement with MEP, but no molecule has been detected so far in the C 3 H 3 NO, C 4 H 4 O, and C 3 H 4 O 2 series; even furan was not detected despite its aromatic electronic structure (Lattelais et al 2010b).…”
Section: Structure and Stability Of Molecular Targetssupporting
confidence: 52%
“…Four out of seven of the aforementioned most stable isomers (noted Isomer Obs. ) have been identified in the ISM in agreement with MEP, but no molecule has been detected so far in the C 3 H 3 NO, C 4 H 4 O, and C 3 H 4 O 2 series; even furan was not detected despite its aromatic electronic structure (Lattelais et al 2010b).…”
Section: Structure and Stability Of Molecular Targetssupporting
confidence: 52%
“…HNC has also been detected in the atmosphere of Titan,8 but attempts to detect the methyl and ethynyl derivatives have failed so far. Under standard laboratory conditions, isocyanides rearrange upon heating to give the thermodynamically more‐stable cyanide isomers;9, 10 however, some photochemical studies revealed the opposite rearrangement under irradiation 11. 12 New spectroscopic studies or improvements upon old studies of such simple isocyanides could provide useful tools for the detection of these species in the various areas of the universe where cyanide isomers have been detected, including the ISM, the atmosphere of Titan, and comets.…”
Section: Introductionmentioning
confidence: 99%
“…, furan18 , thiophene18 , acetonitrile19 , cyanoacetylene 20 , C 4 H 2 + isomers 21 , and C 2 HNS isomers22 .were tested on carbon chains including 1 as a quick and easy way to obtain fundamental vibrational frequencies25 , mostly with a view towards cost effective calculations of much larger molecules formed upon processing of astrochemical species. Electric field gradients and quadrupole coupling constants were calculated for 10 and compared to experimental values 26 in 1992.…”
mentioning
confidence: 99%